PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH DAN KOMUNIKASI MATEMATIK SISWA SMP NEGERI 28 MEDAN MELALUI PEMBELAJARAN INKUIRI DENGAN STRATEGI REACT - Sehat Matua Ritonga (State Islamic University of North Sumatra, 2017)
The purpose of this study was to examine: (1) improvement of problem solving ability of mathematics between students who were given inquiry learning model with REACT strategy with students who were given the usual learning model; (2) improvement of mathematical communication ability between students who are given inquiry learning model with REACT strategy with students who are given the usual learning model. This research was conducted in SMP Negeri 28 Medan with sample of 60 students. This study is a quasi-experimental study with pre-test-post-test control group design. The population in this study were all students of class VIII (eight) by taking samples of two classes (experimental class and control class) through random sampling technique. The instrument used consisted of mathematical problem solving test and mathematical communication skill test. The instrument is said to have fulfilled the terms of content validity and reliability coefficient. Data were analyzed by two-way ANAVA test. Prior to the use of two-track ANAVA test, homogeneity test in the study and normality in this study with 5% significance level. Based on the results of the analysis, the research results are obtained: (1) improvement of problem solving ability of mathematics students who get inquiry learning model with REACT strategy is higher than students who get ordinary learning model; (2) improvement of students' mathematical communication ability that obtains inquiry learning model with REACT strategy is higher than students who get ordinary learning model. Based on the results of this study, researchers suggest that inquiry learning model with REACT strategy can be an alternative for teachers to improve problem solving skills and mathematical communication.